Factors associated with decision-making on prophylactic hysterectomy and attitudes towards gynecological surveillance among women with Lynch syndrome (LS): a descriptive study - Kalamo, Mari H. (Fam Cancer, 2020)
To prevent endometrial carcinoma in Lynch syndrome (LS), regular gynecological surveillance visits and prophylactic surgery are recommended. Previous data have shown that prophylactic hysterectomy is an effective means of cancer prevention, while the advantages and disadvantages of surveillance are somewhat unclear. We aimed to evaluate female LS carriers’ attitudes towards regular gynecological surveillance and factors influencing their decision-making on prophylactic surgery that have not been well documented. Pain experienced during endometrial biopsies was also evaluated. Postal questionnaires were sent to LS carriers undergoing regular gynecological surveillance. Questionnaires were sent to 112 women with LS, of whom 76 responded (68%). Forty-two (55%) had undergone prophylactic hysterectomy by the time of the study. The majority of responders (64/76; 84.2%) considered surveillance appointments beneficial. Pain level during endometrial biopsy was not associated with the decision to undergo prophylactic surgery. The level of satisfaction the women had with the information and advice provided during surveillance was significantly associated with the history of prophylactic hysterectomy (satisfaction rate of 73.2% versus 31.8% of nonoperated women, p = 0.003). The women who had undergone prophylactic surgery were older than the nonoperated women both at mutation testing (median of 42.3 years versus 31.6 years, p < 0.001) and at the time of the study (median of 56.9 years versus 46.0 years, respectively, p < 0.001). Women with LS pathogenic variants have positive experiences with gynecological surveillance visits, and their perception of the quality of the information and advice obtained plays an important role in their decision-making concerning prophylactic surgery.